Using the jackhammer as rock digging method in Gabricar quarry, North Bioko, Equatorial Guinea - Alfonso Alogo Nguema-Mozoho; Maday Cartaya-Pires; Gilberto Sargentón-Romero; Roberto Watson-Quesada (Minería y Geología, 2022)
Blasting and drilling methods are mainly used in basalt rock quarries as blasting-digging methods. The purpose of this study is to argue the validity of using a jackhammer as a rock removal method in Gabricar quarry, based on knowing the geomechanical parameters of rocks as well as the technical-economic indicators for exploitation. Gravimetric, saturation, hydrostatic weighing, pycnometric and axial loads methods were used to obtain physical-mechanical properties of the rocks and geological survey, volumetric joint count, and strength coefficient were used to establish crack elements, block size, and rock mass quality, respectively. 4.75% humidity; 2.39% porosity; 5.73 g/cm3 volumetric mass; density of 26.44 g/cm3 and axial compressive strength of 173.53 Mpa as average values of physical-mechanical properties were obtained. Four families of cracks with spacing of 0.4m, 0.6m; 0.3m and 0.2m and 18mm openings; 13mm; 3mm and 9mm, respectively were established. Blocks are small and the rocky massif is of good quality. The technical-economic analysis showed the efficiency of the jackhammer as a blasting-based digging method in Gabricar quarry.